Synergistic Effects of Seaweed Extract Concentrations and Nitrogen Fertilization Levels on Growth and Yield of Wheat (Triticum aestivum L.) under Semi-Arid Conditions - Alham Mohamed Hassan; Hudi Mohammed Omar; Wajdi Aissa Mohammed (المجلة الأفروآسيوية للبحث العلمي, 2025)
Optimizing nitrogen (N) fertilization is critical for wheat productivity, but challenges regarding nutrient use efficiency persist. Biostimulants, such as seaweed extract (SWE), offer a promising strategy to enhance crop performance. This study investigated the synergistic effects of SWE applied as a seed treatment (coating and priming) and varying N levels (0, 60, 120, and 180 kg N/ha) on the growth, yield, and physiological efficiency of wheat under semi-arid conditions. A split-plot field experiment was conducted where main plots were seed treatments and sub-plots were N levels. Results revealed a significant synergistic interaction (P < 0.05) between SWE application and N fertilization, enhancing final grain yield by up to 36% in the priming treatment compared to the control. This yield increase was primarily attributed to a significant improvement in key yield components, including the number of spikes per m², grains per spike, and thousand-kernel weight. We conclude that integrating SWE seed priming with optimized N fertilization (120–180 kg N/ha) is a potent strategy to enhance wheat productivity. This synergy appears to be driven by an improvement in the plant's Nitrogen Use Efficiency (NUE) and a favorable modulation of yield component trade-offs.